Optimizing selectivity of the Cerebellar Cognitive Affective Syndrome Scale by use of correction formulas, and validation of its German version - Gustafsson Thieme, Andreas Günther; Rubarth, Kerstin; van der Veen, Raquel; Müller, Johanna; Faber, Jennifer; Barkhoff, Miriam; Minnerop, Martina; Elben, Saskia; Huvermann, Dana; Erdlenbruch, Friedrich; Berlijn, Adam M.; Sulzer, Patricia; et al. (Journal of neurology, 2025)
Background: Cerebellar disease may result in Cerebellar Cognitive Affective Syndrome (CCAS). The CCAS-Scale, designed to screen for CCAS, has been validated in English Hoche (Brain 141:248–270, 2018) and adapted to other languages. Methods: Here, the German CCAS-Scale Thieme (Neurol Res Pract 2:39, 2020) was validated in 209 patients with cerebellar disorders and 232 healthy controls. Correction formulas for the outcome parameters [failed test items (range: 1–10) and sum raw score (range: 0–120)] were developed, controlling for age, education, and sex effects. Diagnostic accuracy and reliability were assessed. Results: Correction formulas improved selectivity in controls, reducing false positives (failed items: 40%; sum score: 13% vs. original method Hoche (Brain 141:248–270, 2018): 67%), while maintaining moderate sensitivity (failed items: 69%; sum score: 48% vs. original method Hoche (Brain 141:248–270, 2018): 87%). Word fluency tests differentiated best between patients and controls, while other items did not. Internal consistency (α = 0.71) was acceptable. Removal of word fluency tests worsened it. Retest and interrater reliability were high [intraclass correlation coefficients (ICC): 0.77–0.95]. However, these ICCs yielded a large minimal detectable change (MDC; 2.2–2.4 failed items, 9.5–11.4 raw score points) in patients, limiting the use of the CCAS-Scale in follow-up examinations. Conclusion: The correction formulas improved diagnostic accuracy of the CCAS-Scale, particularly for the sum raw score. Therefore, we recommend using the corrected sum raw score for evaluation instead of the uncorrected number of failed items, proposed originally Hoche (Brain 141:248–270, 2018). Some test items, however, did not differentiate well between patients and controls and MDCs were large, highlighting the need for refined CCAS assessment instruments as progression or treatment outcomes.